2013
DOI: 10.1108/ijppm-jun-2012-0057
|View full text |Cite
|
Sign up to set email alerts
|

A strategic and operational approach to assess the lean performance in radial tyre manufacturing in India

Abstract: Purpose -The purpose of this study is to assess the lean performance of a tyre manufacturing firm in India. The key objective is to find key strategic and operational decision-making dimensions for developing effective lean manufacturing environment in a tyre manufacturing organization. Design/methodology/approach -This research is empirical in nature where the opinions of a group of experts of an Indian tyre manufacturing firm were consulted to formulate an interpretive structural model (ISM) of the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…The literature clearly demonstrates the application of lean principles in achieving performance improvement in process industry in the form of reduction of wastes, improvement in quality, reduction in lead times, reduction in costs, efficient supply chain management and above all, high customer satisfaction (Abdulmalek and Rajgopal 2007;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012;Gupta, Acharya, and Patwardhan 2013). In fact, magnitude of performance improvement through adoption of lean is much higher in process industry than in other industries (Taj and Morosan 2011).…”
Section: Performance Improvement Through Lean Implementationmentioning
confidence: 93%
See 1 more Smart Citation
“…The literature clearly demonstrates the application of lean principles in achieving performance improvement in process industry in the form of reduction of wastes, improvement in quality, reduction in lead times, reduction in costs, efficient supply chain management and above all, high customer satisfaction (Abdulmalek and Rajgopal 2007;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012;Gupta, Acharya, and Patwardhan 2013). In fact, magnitude of performance improvement through adoption of lean is much higher in process industry than in other industries (Taj and Morosan 2011).…”
Section: Performance Improvement Through Lean Implementationmentioning
confidence: 93%
“…Unfortunately, the process industry has not exploited the benefits of lean manufacturing in proportion to its discrete manufacturing counterparts. Several researchers have noted a significant deficit in literature on process industry applications of lean manufacturing (Abdulmalek and Rajgopal 2007;Gabauer, Kickuth, and Friedli 2009;Jain and Lyons 2009;Gupta, Acharya, and Patwardhan 2013). The process industry adopts manufacturing processes such as mixing, separating, forming and chemical reaction, which are generally used to produce non-discrete materials.…”
Section: Production Planning and Control 565mentioning
confidence: 98%
“…Lean practices have been assessed through various frameworks proposed in the academic literature (Panizzolo, 1998;Mady, 2009;Furlan et al, 2011;Shah and Ward, 2003;Nordin et al, 2010;Gupta et al, 2013;Anand and Kodali, 2009). However, Al-Najem et al's (2013) framework was selected as the most appropriate for this study due to it evaluates lean readiness (LR) based on quality practices that are considered enablers of LM (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cause and effect diagram was also used in an Indian study by Gupta et al (2012), although no manufacturing aspects were discussed. One more exploratory research was implemented for finding the enablers for successful implementation of lean tools in radial tire-manufacturing company in India (Gupta et al 2013); however, no manufacturing aspects were discussed in this study also. In the current study, six-sigma DMAIC method is used for improving the process performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Around the world, only few studies have been carried out for the tire industries and these studies are focused on analyzing the profitability of car and truck tire remanufacturing (Lebreton and Tuma 2006), system design for tire reworking (Sasikumar et al 2010), value analysis for scrap tires in cement industries (de Souza and Márcio de Almeida 2013), and analyzing the factors for end-of-life management (Kannan et al 2014). In addition, some researchers proposed methodologies for improving the process in tiremanufacturing companies out of which few industries implemented lean and six-sigma methodologies (Gupta et al 2012(Gupta et al , 2013Visakh and Aravind 2014;Wojtaszak and Biały 2015). Other studies also found implementing just in time (Beard and Butler 2000) and Kanban (Mukhopadhyay and Shanker 2005).…”
Section: Literature Reviewmentioning
confidence: 99%